Rancang Bangun Sistem Penjadwalan Produksi Dengan Menggunakan Metode EARLIEST DUE DATE Pada CV TIDAR JAYA - Citra Prasetya; Dr. Jusak; Valentinus Roby Hananto (Jurnal Sistem Informasi Universitas Dinamika, 2017)
Production scheduling is one of the most important aspect that ensures the business process of a company running smoothly, as well as in CV Tidar Jaya. CV Tidar Jaya in its business has not utilized any production scheduling schemes, it can be seen from their frequent delay of the order completion. The Problem is mainly because they always prioritized special order without looking at which order came first. In addition to that, they only used rough estimation about the completion time without exact calculation. To improve their business processes, we build a production scheduling system using the Earliest Due Date (EDD) method which is able to calculate the date of order completion and to minimize delay. CV Tidar Jaya also uses non-technical factors that are used as reference for calculating the engine machine start up time schedule, machine rest time and production materials time readiness. By using the EDD method, job that has an earliest deadline will be prioritize. Using this scheduling system, CV Tidar Jaya is able to produce information of finishing order time and optimize production scheduling in such a way that the delay can be minimized.